Uma análise bakhtiniana da Proposta Curricular do Estado de São Paulo - Oliveira, Cristiane Alves de (2014)
This thesis has the objective of analyzing a sequence of activities in the Portuguese Language school books. In this work, we aim to present the theoretical precepts which are the foundation of the analytical course of the research object, doing an interactionist reading of the parameterization documents of High School education and conducting a bakhtinian analysis of the material that makes up the Curricula of the State of São Paulo: the Student’s Notebook and the Teacher`s Notebook. Our analysis is founded on the theoretical and philosophical project of the Russian thinker Mikhail Bakhtin, who shows completely original thought about language from a perspective named dialogism, whose outspread are the dialogical relations. We still investigated concepts, like ideological sign, subject, enunciation, and verbal interaction. After going through these domains, fundamental for the understanding of Bakhtin’s saying process, we selected at first the Presentation Letters present on the National Curricula Parameters for High School Education, in Curricula Orientations for High School Education, and in the Curricula of the State of São Paulo, searching for the use of bakhtinian concepts from the choice of two words we judge to be relevant in the educational matter: the word quality and the word teacher. Through the reflections prompted by the analysis of this material, we chose a Learning Situation, entitled “The word makes me…”, present on volume 1 of the first High School year, with the purpose of checking how much quality the material has, apart from investigating how the teacher can be a mediator between the prescribed in the curricula and what is effectively proposed to the student, under a interactionist approach of the language. The results obtained revealed that, despite the curricula tries to make use of bakhtinian concepts in its theoretical assumptions, in practice, Portuguese Language teaching showed a few or none changes: ready lessons are suggested to the teacher to be followed step by step, what implicates in saying that their freedom to plan lessons became limited and, on the other hand, the quality of Portuguese Language teaching, revealed in the analyzed material, is questionable, once the conception one has of language is merely of an abstract system, detached from a real context, not enabling a live interlocution as it happens in the language. Thus, the student does not constitute in the subject of their saying, once opportunities to be the author are not offered to them, to effectively elaborate points of view, world-view, value judgments, what becomes an authoritarian and monological teaching, not enabling the openness for dialogism, which takes into account the point of view and the subject’s values, in special, the student, who is the main subject in the teaching process. Key words: interactionism; teaching; learning situation; word, linguistics.